THE EARLY PRECAMBRIAN GEOLOGICAL EVOLUTION AND THE PROBLEM OF THE "TECTONO-MAGMATIC ACTIVIZATION" IN THE UKRAINIAN SHIELD - KIRILYUK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main tendencies of the Early Precambrian crust development and its thermal are recognized on the example of the Ukrainian Shield. The author arrived at the conclusion that there is a low possibility of the Ukrainian Shield stabilization in a Preriphean time. Probably the tectono-magmatic activization of this structure took place only in the Riphean time, while the phenomena, that usually are considered as the Precambrian activization, are actually result of some remaining processes after the Early Precambrian stage of the shield development.